KAJIAN TENTANG LAMA FERMENTASI NIRA AREN (Arenga pinnata) TERHADAP KELIMPAHAN MIKROBA DAN KUALITAS ORGANOLEPTIK TUAK - Riska Mussa (BIOPENDIX, 2014)
Background: Nira palm (Arenga pinnata) is favored by the people because it can be consumed directly and processed for food. It is characteristic palm juice (A. pinnata) can undergo fermentation because the sugar content is quite high and the presence of yeast in it. Therefore, this study examines the relationship between palm juice fermentation (A. pinnata) with the presence and abundance of microbial and organoleptic quality of wine. Methods: The study was conducted on 2-5 June 2011 in the Basic Biology Laboratory Faculty of Teacher Training and Education Pattimura University. Results: The abundance of yeast is more prevalent at the beginning of fermentation 0-5 hours, amounting to 27.1 x 106 to 48.8 x 106, while the number of bacteria over a lot of yeast in the fermentation time of 10 hours is 21.0 x 106, and after 15 hours, the amount of yeast and bacterial abundance due to a succession of diminishing the number of yeast 12.8 x 106 and 12.3 x 106 bacterial counts. Conclusion: The result of organoleptic quality wine, the color of the indicator does not change while the best indicator of flavor found in the fermentation time 0 hours, and the aroma of the best indicators of the fermentation time of 15 hours.